2016
DOI: 10.1103/physrevx.6.021017
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Topological Edge States in a Large Energy Gap near the Step Edges on the Surface ofZrTe5

Abstract: Two-dimensional topological insulators with a large bulk band gap are promising for experimental studies of quantum spin Hall effect and for spintronic device applications. Despite considerable theoretical efforts in predicting large-gap two-dimensional topological insulator candidates, none of them have been experimentally demonstrated to have a full gap, which is crucial for quantum spin Hall effect. Here, by combining scanning tunneling microscopy/spectroscopy and angle-resolved photoemission spectroscopy, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
209
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(254 citation statements)
references
References 35 publications
28
209
9
Order By: Relevance
“…As will be shown below, the resistivity peak and the thermopower sign reversal at T p can be reproduced by our parameter-free transport calculations when taking into account the intrinsic band structure anisotropies at the valence band maximum and conduction band minimum. Our results also provide a simple physical explanation for the contradictory reports in the literature regarding the electronic structure of ZrTe 5 , i.e., semiconductor versus Dirac semimetal [12][13][14][15][16][17][18].…”
Section: Carrier Density and Mobilitysupporting
confidence: 59%
See 2 more Smart Citations
“…As will be shown below, the resistivity peak and the thermopower sign reversal at T p can be reproduced by our parameter-free transport calculations when taking into account the intrinsic band structure anisotropies at the valence band maximum and conduction band minimum. Our results also provide a simple physical explanation for the contradictory reports in the literature regarding the electronic structure of ZrTe 5 , i.e., semiconductor versus Dirac semimetal [12][13][14][15][16][17][18].…”
Section: Carrier Density and Mobilitysupporting
confidence: 59%
“…The ZrTe 5 single crystals used in the present study were grown by chemical vapor transport for the CVT samples [16] and by the Te-flux method for the Flux samples [18]. We employed iodine (I 2 ) as the transport agent during the CVT crystal growth.…”
Section: A Crystal Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…3 (e), displaying the SX photon energy scan for LV polarization. In this dataset the binding energy of the CEM is −50 meV, which corresponds to the same energy position of panel (a) with respect of the band structure, owing to the temperature dependent energy shift of the band structure [15,19], (see suppl. information [26]).…”
mentioning
confidence: 67%
“…There the interpretation was that ZrTe 5 is a Dirac semimetal and the Dirac fermion splits into pairs of Weyl fermions under the external magnetic effect. However, subsequent photoemission and STM experiments 39,40 clearly revealed that the robust electronic groundstate of ZrTe 5 is that of a gapped semiconductor with a small (∼ 50 meV) gap (not a Dirac semimetal). This suggests that a thorough theoretical understanding of the origins of the negative magneto-resistance in this material is lacking.…”
Section: Transport Response and The Chiral Anomalymentioning
confidence: 99%